2023
DOI: 10.1111/cid.13176
|View full text |Cite
|
Sign up to set email alerts
|

The significance of vertical platform discrepancies and splinting on marginal bone levels for adjacent dental implants

Abstract: Objective: The aim of this retrospective study was to investigate the influence of vertical platform discrepancies for splinted and non-splinted adjacent implants on radiographic marginal bone loss (RMBL). Methods: Data from January 2000 to February 2021 were collected from the electronic charts of 156 patients with 337 implants at the UCSF School of Dentistry. Five different implant restoration categories were evaluated for radiographic evidence of proximal RMBL. Patients with (1) two adjacent single crowns, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Implant placement at a depth of 6 mm or more in relation to the cementoenamel junction of adjacent tooth can increase the risk of peri‐implantitis by 8.5 times (OR = 8.5) 76 . A recent retrospective study 77 showed that adjacent implants placed with a vertical platform discrepancy of more than 0.5 mm have a higher incidence of peri‐implant bone loss. Additionally, splinted adjacent implants with different vertical platform levels are associated with a higher incidence of radiographic marginal bone loss (>1 mm) when compared to non‐splinted restorations.…”
Section: Associated Risk Factors Of Peri‐implant Diseasesmentioning
confidence: 99%
“…Implant placement at a depth of 6 mm or more in relation to the cementoenamel junction of adjacent tooth can increase the risk of peri‐implantitis by 8.5 times (OR = 8.5) 76 . A recent retrospective study 77 showed that adjacent implants placed with a vertical platform discrepancy of more than 0.5 mm have a higher incidence of peri‐implant bone loss. Additionally, splinted adjacent implants with different vertical platform levels are associated with a higher incidence of radiographic marginal bone loss (>1 mm) when compared to non‐splinted restorations.…”
Section: Associated Risk Factors Of Peri‐implant Diseasesmentioning
confidence: 99%